A framework for understanding the evolution of relationship quality and the customer relationship development process. Issue 4 (December 2016) - Atorough, Peter; Salem, Heba
Abstract This paper attempts to develop and empirically test a conceptual model of relationship quality (RQ) in the financial sector from the perspective of the individual consumer (B2C). Based on a review of RQ research, the paper proposes a model of RQ from the customer perspective using the constructs most often examined in empirical RQ research (customer satisfaction, trust and commitment) and considers the relative importance of these dimensions within the stages of the relationship development process (RDP). A survey of 150 bank customers was undertaken in Egypt and the results tested using structural equation modelling. Respondents were selected on a convenience sampling basis and administered a questionnaire instrument for completion. The findings show that there is a strong relationship between the customer's perceived relationship development phase and the perceived RQ. An important contribution of this paper lies in the alternative conceptualization of RQ as composed of three dynamic dimensions which are dependent on the RDP phase or stage. A second contribution is methodological and relates to the development of a modified scale to identify the relationship phases of customers. To the best of the researchers' knowledge, these contributions are unique and have not been made previously to the body of knowledge on service relationship management.